Unravelling the Biohydrogen Production Potential from a Co-Digestion Process of Banana Processing Wastewater and Synthetic Sewage by Anaerobic Fermentation: Performance Evaluation and Microbial Community Analysis - da Costa Freire, Cintia Cristina [UNESP]; Marin, Danieli Fernanda Canaver [UNESP]; da Silva Mazareli, Raissa Cristina; de Freitas, Caroline [UNESP]; Brienzo, Michel [UNESP]; Maintinguer, Sandra Imaculada [UNESP] (Springer Nature, 2024)
Biohydrogen (bioH2) and soluble metabolites products (SMPs) obtention from the co-digestion process of banana processing wastewater (BPW) and synthetic sewage (SS) were investigated. The reactor performance was evaluated by BPW addition with different initial concentrations: 2.0, 5.0, and 9.6 g of total carbohydrate (TC)/L (pure BPW) using SS to complete the working volume. The dark fermentation process was carried out in a 1 L batch reactor operated at 37 °C/52 h and pH 7. The composition of gas and liquid samples (TC, VFAs, alcohols, and pH) were analyzed during reactor operation. The highest bioH2 production yield (210.82 ± 32.07 NmL/g TC) and bioH2 production rate (40.93 ± 7.60 NmL/g TC/h) were obtained at an initial substrate concentration of 2.0 g TC/L. These results indicated that the co-digestion improved carbohydrate utilization and induced a more effective metabolic pathway to bioH2 production. At this condition, the main soluble metabolite products were acetate and butyrate, whereupon Clostridiacae was the main family involved in BPW fermentation. The prediction of functional gene expression evidenced a shift in the mechanisms of SMPs and bio H2 obtention as the initial concentration of substrate changes. Graphical Abstract: (Figure presented.)
Keywords: Functional gene prediction; Organic acids; Renewable hydrogen; Wastewater treatment